2014
DOI: 10.1021/ie402284q
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Gas-to-Liquids Technology with Different Synthesis Gas Production Methods

Abstract: The design and optimization of a gas-to-liquids technology (GTL) is considered, mostly from the view of an optimal choice of a synthesis gas (syngas) production method. Material balance and energy efficiency are calculated for a number of flowsheets, which comprise syngas production by various techniques and Fischer−Tropsch (FT) synthesis of liquid hydrocarbons (LHs). Three different methods are considered for syngas production: combined steam and dry reforming; autothermal reforming; and partial oxidation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…25 The GtL process provides an effective mechanism in increasing the supply of domestic transportation fuels by reducing dependence on oil imports, thus enhancing energy security. 6 Studies have shown that the GtL process exhibits carbon conversion efficiency (i.e., carbon in the feedstock that is converted to fuels) as high as 52%, 26 which is significantly higher than those from CtL (28%-34% 27 ) and BtL (43% 28 ), as shown in Table 1. In addition to high carbon efficiency from GtL, significant drivers for the development of the GtL technology could be attributed to the following factors: 29 • The GtL process has high exothermicity, where the excess heat generated could be configured to produce electricity and steam.…”
Section: Introductionmentioning
confidence: 99%
“…25 The GtL process provides an effective mechanism in increasing the supply of domestic transportation fuels by reducing dependence on oil imports, thus enhancing energy security. 6 Studies have shown that the GtL process exhibits carbon conversion efficiency (i.e., carbon in the feedstock that is converted to fuels) as high as 52%, 26 which is significantly higher than those from CtL (28%-34% 27 ) and BtL (43% 28 ), as shown in Table 1. In addition to high carbon efficiency from GtL, significant drivers for the development of the GtL technology could be attributed to the following factors: 29 • The GtL process has high exothermicity, where the excess heat generated could be configured to produce electricity and steam.…”
Section: Introductionmentioning
confidence: 99%
“…For GtL processes, Ermolaev et al . have reported a carbon efficiency of 52.2% in their modeling studies . Okeke and Adams have studied co‐processing petroleum coke (petcoke) and NG to liquid fuels via FT synthesis and have reported a carbon efficiency of 32–44% .…”
Section: Resultsmentioning
confidence: 99%
“…ATR is the most heat‐efficient technology for natural gas conversion into syngas. Heat released by the POx process, an exothermic reaction, is utilized by the SMR reaction 22,23 . The overall reaction is given by eqns (1) and (2):…”
Section: Syngas Productionmentioning
confidence: 99%